A New Method of Automatic Dimension Analyzer - Vasumathi, G. (International Journal of Psychosocial Rehabilitation, 2018)
The main aim of the project is to measure the dimensions of object in the fully automated way and it can be implemented in the industrial applications mainly in the manufacturing industries, when the object was manufactured it was inspected automatically and can also decide automatically whether the manufactured product is accepted or rejected and also either it may be re machined again. Mainly it was used in the QC department of manufacturing industries.